International perspectives on selection methods of entry into higher education - Andrich, David; Mercer, Annette; Higher Education Council (Australia); Australia. National Board of Employment, Education and Training (Canberra : National Board of Employment, Education and Training [and] Higher Education Council, 1997)
This report provides information and perspectives on a variety of selection methods for entry to higher education currently being used in the United States of America, the United Kingdom, and selected countries of western continental Europe. These countries, which, except for the Netherlands, do not have a tertiary entrance rank or the equivalent for selecting entrants directly from secondary school, provide a broad coverage of systems with which Australian higher education is often compared. In each country, the method of selecting students into higher education reflects both its history and its present needs in secondary and higher education. Most countries are coping with high levels of unemployment and have an increasing proportion of students enrolling in higher education. As part of this accommodation of a changing population, the definition of a university, especially in the United Kingdom and western continental Europe, is broadening. This affects the meaning of selection into universities. The selection process of students from secondary school to university is one of many components in an educational system, and reflects the complex political, social and economic features of a country. For example, the selection system in the United States of America is characterised by being decentralised and controlled by universities within state and federal laws, and reflects a wealthy society which emphasises the individual, a federation of states which guard their independence, and a society which places a high value on education. In many western continental European countries, routine admission following graduation from very selective high schools reflects their history. The admission of all students who graduate from these schools into universities reflects a political response to student protests for greater access in the 1960s. In each case, therefore, the secondary and higher education systems are reviewed briefly in order to place the selection mechanisms into a context. The mechanisms in all countries are under review, with changes perceived to be more or less urgent. A decreasing number of students in the university age group, but an increasing proportion and an increasing number of applicants, are governing the recent changes in the higher education systems and in the selection mechanisms. Aus
Executive summary -- Introduction -- The Project: key tasks -- Rationale for the countries studied -- Processes of data collection -- The Structure and format of the report -- The Project team -- 1. key issues in the evaluation of selection methods -- Levels of competition in selection methods -- Two levels of operation of the selection procedures -- Competition -- Studies in the reliability of predictors of success -- Comparative costs of different mechanisms -- Ranking of costs of various systems -- Diversity of the student profile and steps taken to address bias in the selection mechanism -- Ethnic minorities -- Students with disabilities -- Gender -- Socio-economic status -- mature students -- systems in operation - 2. Countries studied -- Review of the processes in the United States of America -- Secondary education -- Higher education -- Transition from secondary school to college -- Selection mechanisms -- The College Board and the American College Testing Program -- Advanced placement -- Reliability of predictors of success -- Criticisms of use of the present system -- Diversity of the student profile and steps taken to address bias in the selection mechanism -- Costs of the mechanism in the United States of America -- Enrolment in professional and postgraduate programmes -- The Selective universities -- Review of the processes in the United Kingdom -- Secondary education -- The Examining boards -- Higher education -- Traditional pathways to higher education -- Changes to the traditional pathways -- Changes to the A-levels -- The Universities and Colleges Admissions Service -- Content of applications -- The Selection process -- Studies in the reliability of predictors of success -- Diversity of the student profile and steps taken to address bias in the selection mechanism -- Costs of the mechanism in the United Kingdom -- The Future -- Review of the processes in the Western Continental European countries -- Summary of selection procedures -- Appendix 1. Locations visited and persons interviewed -- Appendix 2. The Structure of education in the United States -- Appendix 3. The College, The University of Chicago: the class of 2000: 970 first-year students -- Appendix 4. Publications sponsored by fair test -- Appendix 5. Examinations and certificates at the end of secondary and at the beginning of tertiary in selected European countries -- Appendix 6. The detailed procedure for tertiary selection in the Netherlands -- Appendix 7. Summary of higher education institutions' equity profiles.untry. For exa
Bibliography: p. 69-79.
Keywords: Education -- Europe; Education -- United States; Education -- Australia; Universities and colleges -- Australia -- Admission; Universities and colleges -- Australia -- Entrance requirements